2016
DOI: 10.2215/cjn.05920616
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin and the Risk of AKI: A Systematic Review and Meta-Analysis

Abstract: Our findings suggest that there is a measurable risk of AKI associated with vancomycin, but the strength of the evidence is moderate. A randomized, controlled trial designed to study kidney function as an outcome would be needed to draw unequivocal conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
87
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 53 publications
(54 reference statements)
3
87
0
1
Order By: Relevance
“…There is significant variability in the reported incidence of vancomycin-related AKI, ranging anywhere from 5% to as high as 43% depending on the study population and baseline risk factors [12,13]. Previous studies examining the association of vancomycin with AKI relied on observations from relatively small cohorts of patients, and thus resulting in uncertainty about the causal role of vancomycin in AKI and about what strategies to use to prevent AKI in patients treated with vancomycin [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…There is significant variability in the reported incidence of vancomycin-related AKI, ranging anywhere from 5% to as high as 43% depending on the study population and baseline risk factors [12,13]. Previous studies examining the association of vancomycin with AKI relied on observations from relatively small cohorts of patients, and thus resulting in uncertainty about the causal role of vancomycin in AKI and about what strategies to use to prevent AKI in patients treated with vancomycin [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Following the implementation of these guidelines, reports of rising incidence of VA-AKI have emerged [14-20]. Exposure to vancomycin is now being recognized as a measurable risk for AKI [21]. However, none of those reports describe specific laboratory features of AKI that could be considered unique or characteristic of VA-AKI and that are otherwise not expected to be seen in other forms of AKI.…”
Section: Introductionmentioning
confidence: 99%
“…Vancomycin is the most commonly prescribed antibiotic in US hospitals with recent studies finding approximately one in four patients receive vancomycin during the course of their hospital stay [49]. Among pharmacists, nephrologists and infectious diseases physicians, there is a broad range of beliefs about vancomycin's propensity to cause V-AKI [50]. Previous studies have reported V-AKI rates ranging from less than 5% to greater than 40% and a wide variety of risk factors have been implicated [19,33].…”
Section: Discussionmentioning
confidence: 99%
“…Supratherapeutic levels dramatically increased risk; however, few patients had trough levels above 20 mg/L resulting in imprecise estimates. Vancomycin is predominantly eliminated in the urine by glomerular filtration, therefore a decrease in renal function, from any etiology, will increase vancomycin serum concentrations [19,50]. In addition, changes in serum creatinine are known to lag actual renal injury.…”
Section: Discussionmentioning
confidence: 99%